Avatar, the last airbender. The search - Yang, Gene Luen (Dark Horse Books, 2020)
"When Zuko discovers a clue to Ursa's fate, he enlists the aid of Team Avatar--and enters into a tense alliance with his sister, the deadly and insane Azula--to finally uncover the truth!"--